Шевченкознавча школа С. Смаль-Стоцького: постаті та концепції (кіцмансько-коломийський осередок) - Меленчук, О.В. (Слово і Час, 2019)
У статті здійснено огляд здобутків учнів С. Смаль-Стоцького на шевченкознавчій ниві, які
продовжили справу вивчення та популяризації творчості Т. Шевченка на буковинсько-покутському
просторі. Акцент зроблено на одному з важливих осередків – Кіцмансько-Коломийському,
де жили й працювали випускники Чернівецького університету початку ХХ ст. (О. Цісик,
Д. Николишин, М. Равлюк, М. Харжевський, О. Ковбуз, Б. Левицький та ін.), які розвивали традиції
шевченкознавчого семінару С. Смаль-Стоцького. The paper offers an overview of the achievements of S. Smal-Stotskyi’s students in Shevchenko
studies, which continued, to a greater or lesser extent, to explore and popularize the works of
T. Shevchenko in the cultural space of Bukovyna and Pokuttia. The main accent is made on the
Kitsman-Kolomyia center, where the early 20th century graduates of the Chernivtsi University lived
and worked, O. Tsisyk, D. Nykolyshyn, M. Ravliuk, M. Kharzhevskyi, O. Kovbuz, B. Levytskyi being
among them. They continued to develop the traditions originating from the seminar on Shevchenko
studies conducted by S. Smal-Stotskyi.
Modern scholars recognize that in the second half of the 19th and early 20th centuries the Chernivtsi
University was the leading educational institution in terms of contribution to Shevchenko studies.
Students picked up the instructions of the professor S. Smal-Stotskyi and not only showed interest in
the works by T. Shevchenko but also expressed their views in public, actively engaging in activities
of the national movement that took place outside the university. The work within the circles continued
profound reading of the Kobzar’s works, initiated at the university. The Circle of Kobzar Studies was
one of them; it united university graduates who became teachers of Kitsman high school – Mykola
Ravliuk, Omelian Tsisyk, Pavlo Diakiv, Oleksa Kovbuz, etc. The members of the circle continued
collecting and analyzing the scholarly and critical material that might help in making comprehensive
analysis of Shevchenko’s works. Such activity formed a good basis for teaching and inspiring
students to explore Shevchenko’s legacy that was fundamental for shaping the national outlook and
national consciousness of contemporary Ukrainians. However, the regular research of the works
by T. Shevchenko also played an important role in the Kitsman-Kolomyia center. This direction was
represented mainly by the works of D. Nykolyshyn and O. Tsisyk.